2009
DOI: 10.1590/s1516-84842009005000085
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de pacientes hemofílicos acompanhados em ambulatório de hematologia

Abstract: IntroduçãoHemofilia é uma coagulopatia hereditária recessiva ligada ao sexo, ocorrendo devida à falta ou produção defeituosa de moléculas dos fatores VIII ou IX da coagulação. A deficiência de fator VIII (Hemofilia A) é a mais frequente, ficando com 85% dos casos; já a deficiência do fator IX (Hemofilia B) corresponde a 15% . 1,2A incidência na população mundial é de 1/10.000 (pelo fator VIII) e de 1/30.000 (pelo fator IX) nascimentos do sexo masculino. É caracterizada pela ocorrência de hemorragias que aparec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
2
4
0
19
Order By: Relevance
“…Corroborating this finding, a study conducted in Brazil found that among individuals aged 9-50 years with hemophilia, 69.9% of them were students, but with predominance of incomplete primary school in 45.5% of cases [20]. According to international studies, school absenteeism has played an important role in the lives of individuals with hemophilia, therefore determining low educational levels in this population [20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Corroborating this finding, a study conducted in Brazil found that among individuals aged 9-50 years with hemophilia, 69.9% of them were students, but with predominance of incomplete primary school in 45.5% of cases [20]. According to international studies, school absenteeism has played an important role in the lives of individuals with hemophilia, therefore determining low educational levels in this population [20].…”
Section: Discussionmentioning
confidence: 96%
“…According to international studies, school absenteeism has played an important role in the lives of individuals with hemophilia, therefore determining low educational levels in this population [20]. In this situation, the low level of schooling suggests a predisposition to dental pain and other problems in buccal health due to the little information on the subject [21].…”
Section: Discussionmentioning
confidence: 99%
“…É consequência da falta ou defeito da produção das moléculas dos fatores VIII (hemofilia A) ou IX (hemofilia B) de coagulação. A doença é decorrente de alterações nos genes codificantes destes fatores localizados no braço longo do cromossomo sexual X [Nunes et al 2009]. Na maioria dos casos, é transmitida a indivíduos do sexo masculino pela mãe portadora.…”
Section: Hemofiliaunclassified
“…Sendo assim, o momento de luto, o qual constitui um momento de intensa dor, constitui um objeto de ação da espiritualidade (12)(13) . (14)(15)(16)(17) . Percebe-se, também, que o exercício da espiritualidade pode ser um grande aliado no que se refere ao processo de reabilitação quanto ao abuso e dependência de álcool e outras drogas (18)(19)(20) .…”
Section: A Vivência Da Espiritualidade Em Situações De Saúde E Doençaunclassified